Discovery and Characterization of a New Cold-Active Protease From an Extremophilic Bacterium via Comparative Genome Analysis and in vitro Expression - Perfumo, Amedea; Freiherr von Sass, Georg Johannes; Nordmann, Eva-Lena; Budisa, Nediljko; Wagner, Dirk (Frontiers in Microbiology, 2020)
Following a screening of Antarctic glacier forefield-bacteria for novel cold-active enzymes, a psychrophilic strain Psychrobacter sp. 94-6PB was selected for further characterization of enzymatic activities. The strain produced lipases and proteases in the temperature range of 4-18ºC. The coding sequence of an extracellular serine-protease was then identified via comparative analysis across Psychrobacter sp. genomes, PCR-amplified in our strain 94-6PB and expressed in the heterologous host E. coli. The purified enzyme (80-kDa) resulted to be a cold-active alkaline protease, performing best at temperatures of 20-30ºC and pH 7-9. It was stable in presence of common inhibitors (β mercaptoethanol (β-ME), dithiothreitol (DTT), urea, phenylmethylsulfonyl fluoride (PMSF) and ethylenediaminetetraacetic acid (EDTA)) and compatible with detergents and surfactants (Tween 20, Tween 80, hydrogen peroxide and Triton X-100). Because of these properties, the P94-6PB protease may be suitable for use in a new generation of laundry products for cold washing. Furthermore, we assessed the microdiversity of this enzyme in Psychrobacter organisms from different cold habitats and found several gene clusters that correlated with specific ecological niches. We then discussed the role of habitat specialization in shaping the biodiversity of proteins and enzymes and anticipate far-reaching implications for the search of novel variants of biotechnological products.